Enhanced performance of photovoltaic–thermoelectric coupling devices with thermal interface materials. (November 2020) - Zhang, Jia; Zhai, Han; Wu, Zihua; Wang, Yuanyuan; Xie, Huaqing; Zhang, Mengjun
Abstract: In this study, thermal interface material is used in photovoltaic–thermoelectric coupling device to enhance the utilization of solar energy. An operating system including cooling equipment is established. The output performance evolutions of PV–TE​ coupling device are carried out based on thermal contact resistance under different experimental conditions. The PV–TE coupling devices combine with monocrystalline silicon PV cell and bismuth telluride TEG. Results show that adding TEG could minimize the PV cell temperature increase, hence improving PV cell performance effectively. Results also indicate that, with thermal interface material, the power generation by PV cells increases at least 14% and the power generation by TEG increases at least 60% due to the decreasing thermal contact resistance. Applying thermal interface material enhances the heat transfer in PV–TE coupling device.